Steel wire and method for manufacturing steel wire
By using specific chemical composition and heat treatment processes in the manufacturing process of steel wires, pearlite tissue is formed, and the surface area is treated with skin light rolling to randomly distribute the crystal orientation, which solves the problem of existing steel wires when bending and twisting The problem of fracture has achieved both high strength and toughness.
Patent Information
- Application Number
- CN202380051553.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-03
- Publication Date
- 2025-02-18
AI Technical Summary
Existing steel wires are prone to breaking or destratification when bending and twisting, and it is difficult to take into account high strength and toughness.
During the manufacturing process of steel wire, specific chemical composition and heat treatment processes are used to form pearlite tissues, and the surface area is treated with skin light rolling to randomly distribute the crystal orientation and reduce the proportion of texture.
The steel wire is achieved to take into account the high strength and toughness, improve the tensile strength and torsional characteristics of the steel wire, and reduce the risk of deformation and fracture during bending and torsion.
Smart Images

Figure CN119487230A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a steel wire and a method for producing the steel wire. This application claims priority based on Japanese Application No. 2022-121882 filed on Jul. 29, 2022, and all the contents described in the Japanese Application are incorporated herein by reference. Background Art
[0002] Patent document 1 discloses a steel wire having a wire diameter of 0.05 mm to 0.38 mm and a tensile strength of 3300 MPa to 3900 MPa. Such a steel wire is used, for example, for tire reinforcements. The method for manufacturing the steel wire described in Patent document 1 is as follows. A steel wire rod as a raw material is obtained. The steel wire rod is heated and austenitized by hot rolling, and then cooled and pearlitized. The pearlitized steel wire rod is further combined with wire drawing and troostitizing treatment, thereby being processed into a specified wire diameter. The steel wire rod made into a specified wire diameter is finally subjected to troostitizing treatment. Next, the steel wire rod is subjected to a first wire drawing process. Next, the wire drawing material obtained by the first wire drawing process is subjected to a swaging process. Next, the intermediate wire drawing material obtained by the swaging process is subjected to a second wire drawing process. Steel wire can be obtained by such a manufacturing method.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-186633 Summary of the invention
[0006] The steel wire of the present disclosure is composed of steel, the steel containing 0.9 mass % or more and 1.1 mass % or less of carbon, 0.15 mass % or more and 0.25 mass % or less of silicon, 0.25 mass % or more and 0.35 mass % or less of manganese, and 0.15 mass % or more and 0.25 mass % or less of chromium, with the remainder being iron and inevitable impurities, the steel having a pearlite structure, the diameter of the steel wire being 0.05 mm or more and 0.45 mm or less, the tensile strength of the steel wire being 3900 MPa or more and 4700 MPa or less, and the structure of the surface region from the surface of the steel wire to a depth of 10% of the diameter in a longitudinal cross section of the steel wire having the following structure, the proportion A of the texture in the <100> orientation of the structure 100 、The ratio of the texture in the <110> orientation A 110 And the ratio A of the texture in the <111> orientation 111 The total ratio A is 32% or less, and the ratio A 100 is the area ratio of the grains having a predetermined orientation in the <100> orientation among all the grains in the observation field of the surface region, and the ratio A110 is the area ratio of the grains having a predetermined orientation in the <110> direction among all the grains in the observation field of the surface region, and the ratio A 111 It is the area ratio of the grains having a predetermined orientation in the <111> direction among all the grains in the observation field of the surface region. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 It is a cross-sectional view showing a longitudinal section of a steel wire according to an embodiment. DETAILED DESCRIPTION
[0008] [Description of Embodiments of the Present Disclosure]
[0009] First, embodiments of the present disclosure will be described by way of examples.
[0010] (1) A steel wire according to an embodiment of the present disclosure is composed of steel containing 0.9 mass % or more and 1.1 mass % or less of carbon, 0.15 mass % or more and 0.25 mass % or less of silicon, 0.25 mass % or more and 0.35 mass % or less of manganese, and 0.15 mass % or more and 0.25 mass % or less of chromium, with the remainder being iron and inevitable impurities, the steel having a pearlite structure, the diameter of the steel wire being 0.05 mm or more and 0.45 mm or less, the tensile strength of the steel wire being 3900 MPa or more and 4700 MPa or less, and the structure of a surface region from the surface of the steel wire to a depth of 10% of the diameter in a longitudinal cross section of the steel wire having a structure having a ratio A of a texture in a <100> orientation of the structure 100 、The ratio of the texture in the <110> orientation A 110 And the ratio A of the texture in the <111> orientation 111 The total ratio A is 32% or less, and the ratio A 100 is the area ratio of the grains having a predetermined orientation in the <100> orientation among all the grains in the observation field of the surface region, and the ratio A 110 is the area ratio of the grains having a predetermined orientation in the <110> direction among all the grains in the observation field of the surface region, and the ratio A 111 It is the area ratio of the grains having a predetermined orientation in the <111> direction among all the grains in the observation field of the surface region.
[0011] The steel wire disclosed herein has a total ratio A of 32% or less of the above-mentioned textures, whereby there are few grains oriented in a specific direction in the surface region. In other words, the structure of the surface region is in a state where the crystal orientation is randomly distributed. Such a surface region of the steel wire is easily deformed by bending and twisting. The steel wire having a total ratio A of 32% or less has excellent toughness.
[0012] The steel wire of the present disclosure has a tensile strength of 3900 MPa or more, and thus has high strength. Therefore, the steel wire of the present disclosure has both high strength and toughness.
[0013] The steel wire of the present disclosure has a diameter of 0.05 mm or more and 0.45 mm or less, and thus can achieve weight reduction while ensuring required strength.
[0014] (2) In the steel wire of (1) above, in the observation field of the surface region, the degree of concentration B of the {100} planes may be 100 and the aggregation degree B of the {111} plane 111 The total aggregation degree B is 8.00 or more and 9.70 or less.
[0015] The steel wire having a total aggregation degree B of 8.00 or more and 9.70 or less has both high strength and toughness. 100 and aggregation degree B 111 The degree of aggregation is obtained by summing up.
[0016] (3) In the steel wire according to (1) or (2) above, the total ratio A may be 29% or less.
[0017] According to the above-mentioned structure (3), the toughness is further improved.
[0018] (4) In the steel wire according to (2) above, the total degree of aggregation B may be 8.40 or more and 9.00 or less.
[0019] According to the above-mentioned structure (4), both high strength and toughness can be achieved.
[0020] (5) In any one of the steel wires (1) to (4) above, the steel wire may have a diameter of 0.15 mm or more and 0.42 mm or less.
[0021] According to the above-mentioned structure (5), it is easy to achieve both strength and lightness.
[0022] (6) In the steel wire of (5) above, the diameter of the steel wire may be 0.18 mm or more and 0.30 mm or less.
[0023] According to the above-mentioned structure (6), it is easy to achieve both strength and lightness.
[0024] (7) In any one of the steel wires (1) to (6) above, the steel wire may have a tensile strength of 3960 MPa to 4500 MPa.
[0025] According to the above-mentioned structure (7), the strength is further increased.
[0026] (8) The method for manufacturing a steel wire according to an embodiment of the present disclosure includes the following steps: a step of preparing a raw material composed of steel, wherein the steel contains 0.9 mass % to 1.1 mass % carbon, 0.15 mass % to 0.25 mass % silicon, 0.25 mass % to 0.35 mass % manganese and 0.15 mass % to 0.25 mass % chromium, with the remainder being iron and inevitable impurities; a step of performing a first wire drawing process on the raw material; a step of performing a sorbitizing treatment on a first wire rod subjected to the first wire drawing process; a step of performing a second wire drawing process on the first wire rod subjected to the sorbitizing treatment; and a step of performing skin pass rolling on a second wire rod subjected to the second wire drawing process.
[0027] In the method for manufacturing a steel wire disclosed herein, skin-pass rolling is performed after wire drawing, thereby controlling the orientation of crystal grains in the surface region of the steel wire. Specifically, by skin-pass rolling, the crystal orientation of the surface region becomes randomly oriented, and the proportion of texture in the surface region becomes small. As a result, a steel wire having both high strength and toughness can be obtained.
[0028] (9) In the method for producing a steel wire according to (8) above, in the step of performing skin pass rolling, the second wire rod may be subjected to the skin pass rolling one or more and eight or less times.
[0029] According to the configuration of (9) above, the ratio of the texture in the surface region can be sufficiently reduced.
[0030] (10) In the method for producing a steel wire according to (8) or (9) above, the reduction of area per skin pass rolling may be 1.0% to 6.0%.
[0031] According to the above-mentioned configuration (10), the ratio of the texture in the surface region can be sufficiently reduced.
[0032] [Details of the embodiments of the present disclosure]
[0033] A specific example of the steel wire according to the embodiment of the present disclosure will be described.
[0034] It should be noted that the present invention is not limited to these examples but is shown by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0035] <Steel Wire>
[0036] One of the characteristics of the steel wire of the present embodiment is that the surface region has a specific structure in a longitudinal cross section. Figure 1, the steel wire 1 is described using a three-dimensional orthogonal coordinate system. The longitudinal section of the steel wire 1 is a section parallel to the Y-axis and passing through the center of the steel wire 1. The surface region 10 is a region from the surface of the steel wire 1 to a depth of 10% of the diameter of the steel wire 1. The depth refers to the distance from the surface of the steel wire 1 toward the center. As described below, the surface region 10 of the steel wire 1 of the present embodiment has a specific structure, and thus there are few grains oriented in a specific direction in the surface region 10. That is, the structure of the surface region 10 is in a state where the crystal orientation is randomly distributed. As a result, the steel wire 1 of the present embodiment has high strength and improved torsional properties.
[0037] Reference Figure 1 , the Y axis is parallel to the long axis of the steel wire 1. The X axis and the Z axis are orthogonal to the Y axis respectively.
[0038] (composition)
[0039] The steel wire 1 is made of steel containing 0.9 mass % to 1.1 mass % carbon (C), 0.15 mass % to 0.25 mass % silicon (Si), 0.25 mass % to 0.35 mass % manganese (Mn), and 0.15 mass % to 0.25 mass % chromium (Cr), with the remainder being iron (Fe) and inevitable impurities.
[0040] 〈Carbon (C)〉
[0041] The steel wire 1 contains 0.9 mass % or more and 1.1 mass % or less of C. C is an element that improves the strength of the steel wire 1. The greater the content of C, the greater the strength of the steel wire 1. On the other hand, when too much C is contained, the toughness of the steel wire 1 decreases. The content of C may be, for example, 1.00 mass % or more and 1.05 mass % or less.
[0042] 〈Silicon (Si)〉
[0043] The composition of the steel wire 1 contains 0.15 mass% or more and 0.25 mass% or less of Si. Si is an element effective for deoxidation of steel. In addition, Si is dissolved in ferrite of the pearlite structure, and has the effect of improving the strength of the steel wire 1. When Si is contained excessively, the toughness of the steel wire 1 decreases. The content of Si may be, for example, 0.20 mass% or more and 0.25 mass% or less, or 0.20 mass% or more and 0.23 mass% or less.
[0044] 〈Manganese (Mn)〉
[0045] The composition of the steel wire 1 contains 0.25 mass% or more and 0.35 mass% or less of Mn. Mn is an element effective for deoxidation of steel. In addition, Mn has the effect of improving the hardenability of steel and improving the strength of the steel wire 1. When too much Mn is contained, the toughness of the steel wire 1 decreases. The content of Mn may be, for example, 0.27 mass% or more and 0.33 mass% or less, or 0.30 mass%.
[0046] 〈Chromium (Cr)〉
[0047] The composition of the steel wire 1 contains 0.15 mass% or more and 0.25 mass% or less of Cr. Cr has the effect of improving the strength of the steel wire 1 by refining the interlamellar spacing of the pearlite structure. When too much Cr is contained, pearlite transformation is less likely to occur. The Cr content may be, for example, 0.20 mass% or more and 0.25 mass% or less, or 0.20 mass% or more and 0.21 mass% or less.
[0048] 〈Unavoidable impurities〉
[0049] The composition of the steel wire 1 may contain inevitable impurities. Examples of inevitable impurities include phosphorus (P), sulfur (S), and copper (Cu). The content of each of P and S is preferably 0.025 mass % or less.
[0050] The composition of the steel wire 1 can be determined by, for example, ICP emission spectrometry (Inductively Coupled Plasma Optical Emission Spectrometry).
[0051] (shape)
[0052] The shape of the steel wire 1 can be appropriately selected. The cross section of the steel wire 1 of the present embodiment is a circular round wire. The cross section of the steel wire 1 is a cross section orthogonal to the Y axis. The shape of the cross section of the steel wire 1 can also be non-circular. Non-circular shapes include polygons and ellipses. Polygons include rectangles and hexagons. Rectangles also include squares.
[0053] (diameter)
[0054] The diameter of the steel wire 1 is greater than or equal to 0.05 mm and less than or equal to 0.45 mm. The diameter of the steel wire 1 refers to the diameter of a circle having an area equal to the area of the cross section of the steel wire 1. The steel wire 1 having such a diameter can be applied to reinforcements such as tires. The diameter of the steel wire 1 can also be greater than or equal to 0.15 mm and less than or equal to 0.42 mm, or can also be greater than or equal to 0.18 mm and less than or equal to 0.30 mm.
[0055] (tensile strength)
[0056] The tensile strength of the steel wire 1 is greater than or equal to 3900 MPa and less than or equal to 4700 MPa. The steel wire 1 having such a tensile strength is high-strength and can be applied to reinforcements such as tires. The tensile strength of the steel wire 1 is the maximum stress obtained by stretching the steel wire 1 at a certain speed using a tensile testing machine until the steel wire 1 breaks. For example, a 200 mm test piece taken out of the steel wire 1 is stretched at a tensile speed of 100 mm / min, and the tensile strength is measured until the test piece breaks. The tensile strength of the steel wire 1 can also be greater than or equal to 3900 MPa and less than or equal to 4400 MPa.
[0057] (organize)
[0058] The structure of the steel wire 1 is mainly a pearlite structure. The steel wire 1 is made of steel having the above-mentioned composition and a pearlite structure, thereby achieving both high strength and toughness.
[0059] Generally, steel wire is manufactured by wire drawing. The structure of the steel wire after wire drawing becomes a texture in which the grains extend in the wire drawing direction and the grains are strongly oriented in the length direction of the steel wire. The steel wire with such a texture is not easy to deform when it is bent or twisted. For example, when the steel wire is twisted, it cannot follow the twisting deformation, and the steel wire is easy to break or delamination occurs easily.
[0060] 〈Surface area〉
[0061] (Total ratio of texture)
[0062] The steel wire 1 of the present embodiment has a structure in which the ratio of a texture in which a specific crystal plane is oriented in a specific orientation is small and the crystal orientation is randomly oriented in the surface region 10. The surface region 10 is a region from the surface of the steel wire 1 to a depth of 10% of the diameter of the steel wire 1. The surface region 10 may be a region from the surface of the steel wire 1 to a depth of 5 μm or more and 20 μm or less.
[0063] The ratio A of the texture in the <100> direction in the longitudinal section of the surface region 10 is 100 、The ratio of the texture in the <110> orientation A 110 And the ratio A of the texture in the <111> orientation 111 The total ratio A is 32% or less. That is, the ratio of the remaining part of the surface region 10 other than the above textures is 68% or more. In the <100> orientation texture, the <100> orientation of the grains has a predetermined orientation. Ratio A 100 The ratio A is the area ratio of the grains having a predetermined orientation in the <100> orientation among all the grains in the observation field 30 of the surface region 10. In the <110> orientation texture, the <110> orientation of the grains has a predetermined orientation. 110The ratio A is the area ratio of the grains having a predetermined orientation in the <110> orientation among all the grains in the observation field 30 of the surface region 10. In the <111> orientation texture, the <111> orientation of the grains has a predetermined orientation. 111 It is the area ratio of the grains having a predetermined orientation in the <111> direction among all the grains in the observation field 30 of the surface region 10 .
[0064] Here, the grains having a predetermined orientation in the <100> direction refer to grains whose <100> direction is within 10° with respect to the X-axis and the Z-axis in the longitudinal section. The grains having a predetermined orientation in the <110> direction refer to grains whose <110> direction is within 10° with respect to the X-axis and the Z-axis. The grains having a predetermined orientation in the <111> direction refer to grains whose <111> direction is within 10° with respect to the X-axis and the Z-axis in the longitudinal section.
[0065] The smaller the total ratio A is, the more randomly the crystal orientation is oriented, and therefore the surface area is more susceptible to deformation in response to bending and twisting. The steel wire 1 having a total ratio A of 32% or less has excellent torsional properties. When the total ratio A is further 31% or less, 30% or less, or 29% or less, the torsional properties are further improved. The lower limit of the total ratio A is, for example, 20%. The total ratio A is, for example, 20% or more and 32% or less, further 20% or more and 31% or less, 20% or more and 30% or less, or 20% or more and 29% or less. Ratio A 100 , Ratio A 110 And the ratio A 111 Each is, for example, 4% to 20%, and further, 5% to 18%.
[0066] The ratio of each of the above textures can be obtained by using electron backscatter diffraction (EBSD). Specifically, each ratio is obtained by observing using a FE-SEM (Field Emission Scanning Electron Microscope). Figure 1 The surface region 10 of the longitudinal section of the steel wire 1 is shown, and the crystal orientation of the surface region 10 is analyzed using EBSD. 100It is determined as follows. Determine the orientation of all grains contained in the observation field 30 of the surface area 10. The orientation of the grains is the orientation relative to each direction of the X-axis and the Z-axis. Determine the area ratio of grains whose <100> orientation is within 10° relative to each of the X-axis and the Z-axis among all the grains. The average of the area ratio of grains whose <100> orientation is within 10° relative to the X-axis and the area ratio of grains whose <100> orientation is within 10° relative to the Z-axis is taken as the ratio A. 100 . Ratio A 110 and ratio A 111 It can also be compared with the ratio A 100 In the present disclosure, in any observation field 30 using EBSD, the area ratio of grains with <111>, <110>, and <100> orientations each within 10° may be 32% or less relative to the entire area of the observation field 30 .
[0067] The observation field of view 30 can select any position within the surface area 10. The size of the observation field of view 30 is, for example, a length along the Y axis of 50 μm or more and 150 μm or less, and a length along the X axis of 5 μm or more and 30 μm or less. It can also be a length along the Y axis of 100 μm and a length along the X axis of 20 μm. The observation magnification can be appropriately selected according to the grain size. The observation magnification can be, for example, 9000 times or more. The observation field of view 30 can also be formed by connecting multiple observation fields of view. The longitudinal section of the steel wire 1 is preferably ground. The longitudinal section can also be processed using a cross-section polishing machine, for example.
[0068] (Agglomeration)
[0069] In terms of the organization of the surface region 10, the degree of aggregation B of the {100} planes in the longitudinal section is 100 and the aggregation degree B of the {111} plane 111 The total aggregation degree B can be, for example, 8.00 or more and 9.70 or less. When the total aggregation degree B is 8.00 or more and 9.70 or less, both high torsion characteristics and high tensile strength can be achieved. The total aggregation degree B can also be 8.10 or more and 9.60 or less, or 8.40 or more and 9.00 or less. 100 and aggregation degree B 111 Each is, for example, 4.00 or more and 5.50 or less.
[0070] Aggregation B 100 and aggregation degree B 111It is obtained based on the pole figures of the {100} plane and the {111} plane. The pole figure is a diagram obtained by stereoscopic projection of the distribution of the crystal orientation of the corresponding crystal plane. In the pole figure, the distribution of the crystal orientation is represented by the ratio of the number of grains of the crystal orientation of the corresponding crystal plane in the observation field to the number of grains in the sample with random distribution of the crystal orientation. In other words, the pole figure is an indicator of the aggregation degree of the relative crystal orientation relative to the random organization. An aggregation degree of 1 means the same as the random organization. The greater the aggregation degree is than 1, the more crystals are oriented in the crystal orientation compared to the random organization. When the aggregation degree is represented by contour lines based on the distribution of the aggregation degree obtained from the pole figure, multiple maximum points of different heights appear in the pole figure. The above sample does not have a specific orientation. The above sample is obtained, for example, by heat treating a steel wire at a high temperature. The ratio of grains in the <100>, <110> and <111> orientations to an ideal randomly oriented sample can be obtained by calculation. The ratio of the calculated values was taken as the degree of clustering of the pole figures.
[0071] Specifically, the aggregation degree B 100 and aggregation degree B 111 It is defined as follows. Aggregation degree B 100 It is the largest maximum point in the pole graph of the {100} face. Aggregation B 111 It is the largest maximum point in the pole graph of the {111} plane.
[0072] (use)
[0073] The steel wire 1 of the present embodiment can be applied to reinforcements embedded in rubber products such as tires. Examples of rubber products other than tires are conveyor belts, handrails of escalators, hoses, and the like. The steel wire 1 of the present embodiment has high tensile strength, so strength can be ensured even if it is thin, thereby achieving lightweight rubber products. The steel wire 1 of the present embodiment has high torsional characteristics, so the steel wire 1 is not easy to break during the twisting process, and the steel wire 1 is not easy to delaminate. In addition, even if the steel wire 1 is twisted during use of the rubber product, the steel wire 1 is not easy to break, and the steel wire 1 is not easy to delaminate.
[0074] <Method for manufacturing steel wire>
[0075] The steel wire 1 of the embodiment can be manufactured by the method for manufacturing a steel wire of the embodiment. The method for manufacturing a steel wire of the embodiment includes a first step, a second step, a third step, a fourth step, and a fifth step. Each step will be described in detail below.
[0076] (First process)
[0077] The first step is a step of preparing a raw material composed of steel. The composition of the steel contains more than 0.9 mass % and less than 1.1 mass % carbon, more than 0.15 mass % and less than 0.25 mass % silicon, more than 0.25 mass % and less than 0.35 mass % manganese, and more than 0.15 mass % and less than 0.25 mass % chromium, and the remainder is iron and inevitable impurities. The composition of the wire is the same as that of the steel wire to be manufactured. The raw material is a raw material manufactured by a method such as continuous casting, continuous casting and rolling. The raw material can also be processed into a specified diameter by hot rolling, for example. The diameter of the raw material is, for example, more than 4 mm and less than 6 mm. The shape of the raw material is, for example, a round wire with a circular cross section.
[0078] (Second process)
[0079] The second step is a step of performing a first wire drawing process on the raw material. The first wire drawing process is performed once or multiple times using a die until the diameter of the raw material reaches a specified diameter. The first wire drawing process is performed, for example, in a wet manner. The cross-sectional shrinkage rate of each time of the first wire drawing process is, for example, greater than 10% and less than 20%. The cross-sectional shrinkage rate of each time refers to the ratio obtained by dividing the difference between the cross-sectional area of the raw material before passing through the die and the cross-sectional area of the raw material after passing through the die by the cross-sectional area of the raw material before passing through the die when the raw material passes through a die. Through the second step, a first wire rod subjected to the first wire drawing process can be obtained. The diameter of the first wire rod is, for example, greater than 1 mm and less than 2.5 mm.
[0080] The total reduction of area in the first wire drawing is, for example, 70% to 90%. The total reduction of area in the first wire drawing is a ratio obtained by dividing the difference between the cross-sectional area of the raw material before the first wire drawing and the cross-sectional area of the first wire rod after the first wire drawing by the cross-sectional area of the raw material.
[0081] (Third process)
[0082] The third process is a process of performing a troostitizing treatment on the first wire rod that has undergone the first wire drawing process. The troostitizing treatment is a heat treatment for making the steel constituting the first wire rod into a pearlite structure. In the troostitizing treatment, after heating the first wire rod to make the steel into an austenite structure, the first wire rod is cooled to make the steel into a pearlite structure. Specifically, the troostitizing treatment firstly maintains the first wire rod heated to the austenitizing temperature region for a certain period of time to austenitize the steel. The austenitizing temperature region is a temperature region above the austenitizing temperature, that is, a temperature region above the Acm point. The austenitizing temperature region is, for example, above 950°C and below 1000°C. The holding time in the austenitizing temperature region is, for example, above 5 seconds and below 10 seconds. Next, the austenitized first wire rod is rapidly cooled to the pearlite transformation temperature region and maintained for a certain period of time to pearlitize the steel. The pearlite transformation temperature range is a temperature range lower than the austenitizing temperature and higher than the temperature at which the martensite transformation starts, that is, a temperature range above the Ms point. The pearlite transformation temperature range is, for example, 500°C or more and 600°C or less. The holding time in the pearlite transformation temperature range is, for example, 3 seconds or more and 10 seconds or less. Through such a sorbitizing treatment, the steel becomes a fine pearlite structure. After being held in the pearlite transformation temperature range, the first wire rod is cooled to room temperature. In the austenitizing treatment, in order to suppress the occurrence of decarburization, the first wire rod may also be heated in an inert gas atmosphere.
[0083] (Fourth process)
[0084] The fourth step is a step of performing a second wire drawing process on the first wire rod subjected to the sorbitizing treatment. The second wire drawing process is performed once or multiple times using a die until the diameter of the first wire rod becomes a diameter close to the diameter of the steel wire to be manufactured. The conditions of the second wire drawing process are the same as those of the first wire drawing process. Through the fourth step, a second wire rod subjected to the second wire drawing process can be obtained. The diameter of the second wire rod is a diameter slightly smaller than the diameter of the steel wire. The diameter of the second wire rod is, for example, greater than 0.05 mm and less than 0.45 mm.
[0085] The total reduction of area of the second wire drawing after the sorbitizing treatment is, for example, 95% or more and 99.5% or less. The total reduction of area of the second wire drawing refers to the ratio obtained by dividing the difference between the cross-sectional area of the first wire rod before the second wire drawing and the cross-sectional area of the second wire rod after the second wire drawing by the cross-sectional area of the first wire rod. The total reduction of area of the second wire drawing is 95% or more, thereby obtaining a high-strength steel wire with a tensile strength of 3900 MPa or more.
[0086] (Fifth step)
[0087] The fifth step is to perform skin pass rolling on the second wire rod subjected to the second wire drawing process. Skin pass rolling is a rolling process performed at a very small cross-sectional reduction ratio. By performing skin pass rolling, the orientation of the crystal grains in the surface region of the steel wire can be changed. Through this step, the steel wire 1 of the present embodiment having a specific structure in the surface region can be obtained.
[0088] Skin smooth rolling is performed once or multiple times using a mold. Skin smooth rolling can be performed in a wet process or in a dry process. Skin smooth rolling is preferably performed in a wet process. By performing skin smooth rolling more than once, the crystal orientation of the surface area of the steel wire becomes randomly oriented, and the total ratio A of the above-mentioned texture becomes smaller compared to the case where skin smooth rolling is not performed. The number of skin smooth rollings can be, for example, more than one and less than eight times. The more the number of skin smooth rollings, the smaller the total ratio A becomes. If the number of skin smooth rollings is less than eight times, the time required for skin smooth rolling can be shortened, and productivity is improved. The number of skin smooth rollings can further be more than two times and less than eight times, or more than three times and less than eight times.
[0089] The cross-sectional reduction ratio of each skin-pass rolling is, for example, 1.0% to 6.0%. The cross-sectional reduction ratio of each time refers to the ratio obtained by dividing the difference between the cross-sectional area of the second wire before passing through the die and the cross-sectional area of the second wire after passing through the die by the cross-sectional area of the second wire before passing through the die when the second wire passes through a die. The cross-sectional reduction ratio of each skin-pass rolling is 1.0% to 6.0%, so that the crystal orientation of the surface area of the steel wire is easily randomly oriented, and the total ratio A is easily controlled to be 32% or less. The cross-sectional reduction ratio of each skin-pass rolling can further be 1.5% to 5.5%, 1.5% to 5.0%, or 1.5% to 4.0%. The total cross-sectional reduction ratio of skin-pass rolling is, for example, 7.7% to 39.0%. The total reduction of area after skin pass rolling refers to a ratio obtained by dividing the difference between the cross-sectional area of the second wire rod before skin pass rolling and the cross-sectional area of the steel wire after skin pass rolling by the cross-sectional area of the second wire rod.
[0090] The approach angle of the die used in skin-pass rolling is, for example, 2° to 10°. The approach angle is 2° to 10°, thereby making it easy to orient the crystal orientation of the surface region of the steel wire randomly. The approach angle is further 3° to 8°.
[0091] The skin pass rolling may be performed continuously with the second wire drawing process, or may be performed after the second wire rod subjected to the second wire drawing process is temporarily coiled.
[0092] [Test Example 1]
[0093] The steel wire samples were produced and evaluated.
[0094] (Sample Preparation)
[0095] The steel wires of samples No. 1 to No. 15 were produced by the above-mentioned steel wire manufacturing method. Here, a raw material composed of steel of composition A or composition B shown in Table 1 was prepared. The content of each element shown in Table 1 is a value when the total content of the elements contained in the steel is set to 100 mass%. In Table 1, "bal." in the "Fe" column represents the remainder. The raw material is a raw material produced by melting and casting steel and then hot-rolling it into a wire shape. The shape of the raw material is a round wire. The diameter of the raw material is 5.0 mm.
[0096] The raw material is subjected to a first wire drawing process to obtain a first wire rod. The shape of the first wire rod is a round wire. The diameter of the first wire rod is 1.4 mm. The first wire drawing process is performed in a wet process. The cross-sectional shrinkage rate of each first wire drawing process is set to be greater than 10% and less than 30%. The number of times of the first wire drawing process is 10 times.
[0097] The first wire rod subjected to the first wire drawing process is subjected to a troostitizing treatment. The troostitizing treatment is performed by heating the first wire rod to 980°C in a heating furnace and holding it for 8 seconds, and then immediately placing it in a cooling tank and cooling it to 580°C and holding it for 10 seconds. Thereafter, the first wire rod is cooled to room temperature. The first wire rod is heated in an inert gas atmosphere.
[0098] The second wire rod is subjected to a second wire drawing process on the first wire rod subjected to the sorbitizing treatment to obtain a second wire rod. The shape of the second wire rod is a round wire. The diameter of the second wire rod is a diameter close to the diameter of the steel wire to be produced. The second wire drawing process is performed in a wet manner. The cross-sectional reduction rate of each second wire drawing process is set to be greater than 10% and less than 20%. The number of times the second wire drawing process is performed is 24 times. The total cross-sectional reduction rate from the start of the first wire drawing process to the end of the second wire drawing process is greater than 95%. The total number of times the first wire drawing process and the number of times the second wire drawing process is performed is greater than 20 times.
[0099] The second wire rod subjected to the second wire drawing process was subjected to skin-pass rolling to obtain steel wires of samples No. 1 to No. 15. The shape of the steel wire was round wire. The skin-pass rolling was performed in a wet process. The feed angle of the die was 5°. The number of skin-pass rolling times and the cross-sectional reduction rate of each skin-pass rolling are shown in Table 2.
[0100] The diameters and compositions of the steel wires of the produced samples No. 1 to No. 15 are shown in Table 2. In Table 2, the composition of Table 1 is shown in the column of "Composition".
[0101] The steel wires of samples No. 16 to No. 20 were manufactured in the same manner as the steel wires of samples No. 1 to No. 15 except that skin pass rolling was not performed. The diameters and compositions of the steel wires of samples No. 16 to No. 20 are shown in Table 2. Since skin pass rolling was not performed in samples No. 16 to No. 20, in Table 2, the column of "Number of times of skin pass rolling" is set to "0" and the column of "Reduction of area" is set to "-".
[0102] (Evaluation of Samples)
[0103] 〈Analysis of Organization〉
[0104] The structure of the steel wire of each sample was analyzed. A test piece for analysis was made from the steel wire of each sample. The length of the test piece was 20 mm. After the test piece was embedded in the resin, the test piece was cross-sectioned using a cross-section polisher to expose the longitudinal section of the steel wire. The conditions of the cross-section polisher were set to: an acceleration voltage of 6 kV and an irradiation current of 130 μA. In the finishing of the cross section, the acceleration voltage was set to 1 kV.
[0105] The longitudinal section of the test piece was observed by FE-SEM, and the structure of the surface area was analyzed. The FE-SEM used was Gemini450 manufactured by ZEISS. The observation conditions were set as follows: the magnification was 300 times, the acceleration voltage was 15kV, the irradiation current was 21nA, and the working distance (WD: Work Distance) was 14.5mm. The observed area was set to the range from the surface of the steel wire to a depth of 20μm. The size of the observation field was 100μm in length along the Y axis × 20μm in length along the X axis. The structure within the observation field was analyzed, and it was confirmed that all samples were pearlite structures.
[0106] 〈Analysis of crystal orientation〉
[0107] The longitudinal section of the test piece was observed using FE-SEM, and the crystal orientation of the surface area was analyzed using the EBSD provided by FE-SEM. The EBSD used was Symmetry manufactured by Oxford Instruments. The observation conditions were set as follows: the acceleration voltage was 15 kV, and the irradiation current was 10 nA. The EBSD conditions were set as follows: the integration time was 0.3 msec, the pixel merging (binning) was 4×4, the working distance (WD) was 15 mm, the step length was 0.04 μm, and the tilt angle was 70°. The size of the observed area and the observation field of view were the same as the range of the tissue analysis.
[0108] (Total ratio of texture)
[0109] In the observation field, the ratio A of the texture in the <100> direction is calculated by analysis software. 100、The ratio of the texture in the <110> orientation A 110 And the ratio A of the texture in the <111> orientation 111 Then, find the ratio A 100 , Ratio A 110 And the ratio A 111 The results are shown in Table 2.
[0110] (Agglomeration)
[0111] Furthermore, the pole figures of the {100} face and the {111} face were obtained by analysis software. The degree of aggregation B of the {100} face was calculated based on each pole figure. 100 and the aggregation degree B of the {111} plane 111 Then, the aggregation degree B is calculated 100 and aggregation degree B 111 The results are shown in Table 2.
[0112] <tensile strength>
[0113] The tensile strength of the steel wire of each sample was measured. The steel wire was cut to produce a test piece for the tensile test. The length of the test piece was 200 mm. The test piece was stretched at a tensile speed of 100 mm / min using a tensile testing machine, and the tensile strength until the test piece broke was measured. The results are shown in Table 2.
[0114] 〈Torsion characteristics〉
[0115] The torsion characteristics of the steel wire of each sample were evaluated. The steel wire was cut to make a test piece for the torsion test. The length of the test piece is 100 times the diameter, that is, diameter × 100 mm. Using an electric torsion tester, the test piece was twisted in one direction while tension was applied to the test piece, and the number of twists until the test piece broke was measured. The number of twists counts one turn as one. This number of twists is called the twist value. The torsion speed is set to 30 rpm. The torsion speed is the number of rotations within 1 minute. The tension is set to less than 5% of the yield stress of the steel wire. The yield stress of the steel wire is determined by a tensile test. The twist values of each sample are shown in Table 2. In addition, the number of twists until delamination occurs is measured. When delamination occurs during the torsion test, the torque of the torsion tester decreases. By measuring this torque, it can be confirmed whether delamination has occurred. The number of twists until delamination occurs for each sample is shown in the "Number of Delamination Occurrences" column in Table 2. In the case where delamination did not occur and lead to fracture, the column of “Number of delamination occurrences” is set to “-”.
[0116] [Table 1]
[0117]
[0118] [Table 2]
[0119]
[0120] As shown in Table 2, the twist values of the steel wires of samples No. 1 to No. 15 that were subjected to skin-pass rolling more than once were more than 15 times, and no delamination occurred until the breakage. Therefore, the steel wires of samples No. 1 to No. 15 have high torsional characteristics. The twist values of all the steel wires of samples No. 1 to No. 15 except samples No. 8 and No. 10 are more than 20 times, and have higher torsional characteristics. In addition, the tensile strength of the steel wires of samples No. 1 to No. 15 is more than 3900 MPa, and also has high tensile strength. The steel wires of samples No. 1 to No. 15 are high-strength and excellent in torsional characteristics.
[0121] The surface regions of the steel wires of Samples No. 1 to No. 15 all have specific structures. Specifically, the total ratio A of these steel wires is 32% or less. In addition, the total aggregation degree B of these steel wires also satisfies the range of 8.00 or more and 9.70 or less.
[0122] In contrast, although the steel wires of samples No. 16 to No. 20 that were not subjected to skin-pass rolling had a twist value of 15 or more, delamination occurred before breaking. The delamination occurred less than 3 times in these steel wires, and delamination occurred in the initial stage. In addition, the maximum twist value among these steel wires was 18 times. The torsional characteristics of the steel wires of samples No. 16 to No. 20 were poor. The total ratio A of the steel wires of samples No. 16 to No. 20 was all more than 33%. In addition, the total aggregation degree B of these steel wires also deviated from the range of more than 8.00 and less than 9.70.
[0123] From the above, it is known that a steel wire having a specific structure in the surface region has both high strength and toughness. In addition, it is known that such a steel wire can be obtained by performing skin pass rolling after the final wire drawing process.
[0124] In addition, the following can be understood from the results of Test Example 1. When comparing samples of steel wires of the same diameter and composition, if the cross-sectional reduction ratio of skin-pass rolling is the same, there is a tendency that the more times of skin-pass rolling, the smaller the total ratio A becomes. This tendency can be understood, for example, from the comparison of samples No. 5, No. 6, and No. 7. In addition, from the comparison of samples No. 8 and No. 9 and the comparison of samples No. 10 and No. 11, it can be considered that if the cross-sectional reduction ratio of skin-pass rolling is 5% or less, the total ratio A can be further reduced.
[0125] Description of Reference Numerals
[0126] 1: Steel wire;
[0127] 10: surface area;
[0128] 30: Observe the field of vision.
Claims
1. A steel wire, which is composed of steel, wherein the steel contains: 0.9 mass % or more and 1.1 mass % or less of carbon, 0.15 mass % or more and 0.25 mass % or less of silicon, 0.25 mass % or more and 0.35 mass % or less of manganese, and 0.15 mass% or more and 0.25 mass% or less of chromium, The remainder is iron and unavoidable impurities. The steel has a pearlite structure, The diameter of the steel wire is not less than 0.05 mm and not more than 0.45 mm, The tensile strength of the steel wire is greater than or equal to 3900 MPa and less than or equal to 4700 MPa. In the structure of the surface region from the surface of the steel wire to a depth of 10% of the diameter in the longitudinal cross section of the steel wire, <100> Aspect ratio of texture A 100 、The ratio of the texture in the <110> orientation A 110 And the ratio A of the texture in the <111> orientation 111 The total ratio A is less than 32%, The ratio A 100 is the area ratio of the grains having a predetermined orientation in the <100> direction among all the grains in the observation field of the surface region, The ratio A 110 is the area ratio of the grains having a predetermined orientation in the <110> direction among all the grains in the observation field of the surface region, The ratio A 111 It is the area ratio of the grains having a predetermined orientation in the <111> direction among all the grains in the observation field of the surface region.
2. The steel wire according to claim 1, wherein In the observation field of the surface area, the concentration B of the {100} planes is 100 and the aggregation degree B of the {111} plane 111 The total aggregation degree B is 8.00 or more and 9.70 or less.
3. The steel wire according to claim 1 or 2, wherein: The total ratio A is 29% or less.
4. The steel wire according to claim 2, wherein: The total aggregation degree B is 8.40 or more and 9.00 or less.
5. The steel wire according to any one of claims 1 to 4, wherein The diameter of the steel wire is greater than or equal to 0.15 mm and less than or equal to 0.42 mm.
6. The steel wire according to claim 5, wherein The diameter of the steel wire is 0.18 mm or more and 0.30 mm or less.
7. The steel wire according to any one of claims 1 to 6, wherein The tensile strength of the steel wire is greater than or equal to 3960 MPa and less than or equal to 4500 MPa.
8. A method for manufacturing a steel wire, comprising the following steps: A step of preparing a raw material composed of steel containing 0.9 mass % to 1.1 mass % carbon, 0.15 mass % to 0.25 mass % silicon, 0.25 mass % to 0.35 mass % manganese, and 0.15 mass % to 0.25 mass % chromium, with the remainder being iron and unavoidable impurities; A step of performing a first wire drawing process on the raw material; A step of performing a sorbitization treatment on the first wire rod subjected to the first wire drawing process; A step of performing a second wire drawing process on the first wire rod subjected to the sorbitizing treatment; as well as A step of performing skin pass rolling on the second wire rod subjected to the second wire drawing process.
9. The method for manufacturing a steel wire according to claim 8, wherein: In the step of performing skin pass rolling, the second wire rod is subjected to the skin pass rolling one or more times and eight or less times.
10. The method for manufacturing a steel wire according to claim 8 or 9, wherein: The reduction of area per skin pass rolling is 1.0% to 6.0%.
Citation Information
Patent Citations
Steel wire and producing method for steel wire thereof
JP2017186633A
Communication device, terminal device, and active optical cable
JP2022121882A